Junior High School Students Actively Learn PPKN: Is There Any Reinforcement and Reward Contribution? - Nayottama, Rosy Hera; Patmisari, P (Universitas Muhammadiyah Surakarta, 2023)
This study aimed to determine the effect of reinforcement and reward on student learning activity in PPKn learning in junior high school. This study used quantitative methods with a correlational design. The sample in this study was 245 students of Muhammadiyah Junior High School in Surakarta City, with a quota purposive random sampling technique. Data collection using a closed questionnaire with a Likert scale. Data analysis techniques use multiple regression analysis with the help of SPSS 26 for Windows software. The results showed that (1) reinforcement significantly affected student learning activity in PPKn learning in junior high school, with a significance value of 0.006 < 0.05 and a calculated count of 2.791 > ttable 1.969. Student learning activity in PPKN learning in junior high school is influenced by the reinforcement provided by teachers in the form of verbal and non-verbal support ; (2) the provision of rewards has a significant effect on student learning activity in PPKn learning in junior high school, with a significance value of 0.029 < 0.05 and a calculated tcount of 2.193 > ttable 1.969. Student learning activity in PPKn learning in junior high school is influenced by the provision of rewards made by teachers in the form of gestures, words, deeds, awards in the form of objects, respect, symbolic awards, and praise; (3) there is a joint influence of reinforcement and reward on student learning activity in PPKn learning in junior high school, with a significance value of 0.000 < 0.05 and Fcount 24.786 > Ftable 3.03. The contribution of 17%. In comparison, the remaining 83% is influenced by other factors not studied in this study.